Satisfaction with Life across Countries: Happiness Index and Life Quality Index - Svetlana V. Plyasova; Lyudmila V. Pavlova; Alexander A. Abalakin; Timofey V. Bashlykov (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
Globalization, new technologies, the COVID-19 pandemic, and international military conflicts keep affecting human lives across the globe. The article offers a comparative analysis of life satisfaction against such social indicators as happiness and life quality. Satisfaction with life is associated with pro-government attitudes and social stability, which makes it a useful tool in defining the relevant public opinions about the current global events. The concept of life satisfaction was identified in its connection with achieving happiness and improving the quality of life. The authors assessed the impact of external factors on life satisfaction before the pandemic (2015–2017), during the pandemic (2019–2021) and after the pandemic (2021–2023) across countries to identify the changes brought about by public policy measures. The data obtained by standard research methods were subjected to statistical analysis to conduct a cross-country comparison and the method of time series to identify the chronological changes. The authors summarized various theoretical approaches to the concept of satisfaction with life, Life Quality Index, and Happiness Index. The results may help public authorities in selecting effective managerial decisions in public policy.